Evolution of a concept. Postmodern adolescence - Pierangelo Barone (University of Bologna, 2021)
The main thesis that is discussed in this article is based on the criticism of the prevalent interpretative models of adolescence developed during the twentieth century. Models that today appear inadequate in grasping the socio-cultural and educational transformations that deeply mark the ways of experiencing adolescents born in the second millennium. The effects of the historical and social practices that shape the adolescent experience in the 2000s represent an essential key to understanding the forms that the adolescent system assumes because of social, cultural, economic, historical, and material changes.